2013
DOI: 10.1186/1750-1172-8-100
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional consequences of haploinsufficiency of genes from exocyst and retinoic acid pathway due to a recurrent microdeletion of 2p13.2

Abstract: BackgroundRare, recurrent genomic imbalances facilitate the association of genotype with abnormalities at the “whole body” level. However, at the cellular level, the functional consequences of recurrent genomic abnormalities and how they can be linked to the phenotype are much less investigated.Method and resultsWe report an example of a functional analysis of two genes from a new, overlapping microdeletion of 2p13.2 region (from 72,140,702-72,924,626). The subjects shared intellectual disability (ID), languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Although disruption of MUNC18-1 is most closely associated with Ohtahara syndrome, de novo mutations in MUNC18-1 have also been identified in individuals with severe intellectual disability and non-syndromic epilepsy, individuals with non-syndromic intellectual disability, and individuals with Rett syndrome (Hamdan et al, 2011(Hamdan et al, , 2009Olson et al, 2015;Romaniello et al, 2015). Likewise, recent studies have revealed possible connections between mutations in exocyst genes and neurological disorders (Evers et al, 2014;Frühmesser et al, 2013;Wen et al, 2013). Given that dendrite defects are the strongest pathological correlate of intellectual disability (Kaufmann and Moser, 2000), we speculate that dendritic abnormalities might contribute to intellectual disability that is associated with MUNC18-1 and exocyst dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although disruption of MUNC18-1 is most closely associated with Ohtahara syndrome, de novo mutations in MUNC18-1 have also been identified in individuals with severe intellectual disability and non-syndromic epilepsy, individuals with non-syndromic intellectual disability, and individuals with Rett syndrome (Hamdan et al, 2011(Hamdan et al, , 2009Olson et al, 2015;Romaniello et al, 2015). Likewise, recent studies have revealed possible connections between mutations in exocyst genes and neurological disorders (Evers et al, 2014;Frühmesser et al, 2013;Wen et al, 2013). Given that dendrite defects are the strongest pathological correlate of intellectual disability (Kaufmann and Moser, 2000), we speculate that dendritic abnormalities might contribute to intellectual disability that is associated with MUNC18-1 and exocyst dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] EXOC6B haploinsufficiency has been suggested as a cause for intellectual disability (ID). 10 A homozygous loss-of-function EXOC6B variant in siblings with a skeletal disorder and heterozygosity of the same in healthy parents contrast with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al reported partially overlapping microdeletions involving 2p13.2 in two boys with ID, hyperactivity, ear malformations, and vertebral and/or craniofacial abnormalities [Wen et al, 2013]. One of the patients had a de novo 4 Mb deletion of 2p13.1-p13.3 comprising EXOC6B and 61 other genes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients had a de novo 4 Mb deletion of 2p13.1-p13.3 comprising EXOC6B and 61 other genes. The other one (Patient 1 in Wen et al, 2013) had a small de novo deletion of 0.78 Mb at 2p13.2-13.3 (bp positions converted to hg19: 72,287,071,118) including only two genes: EXOC6B and CYP26B1 (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation